1999
DOI: 10.1073/pnas.96.7.3757
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Saccharomyces cerevisiae centromeric DNA ( CEN DNA)–binding factor 3 (CBF3) kinetochore complex by using atomic force microscopy

Abstract: Yeast centromeric DNA (CEN DNA) binding factor 3 (CBF3) is a multisubunit protein complex that binds to the essential CDEIII element in CEN DNA. The four CBF3 proteins are required for accurate chromosome segregation and are considered to be core components of the yeast kinetochore. We have examined the structure of the CBF3-CEN DNA complex by atomic force microscopy. Assembly of CBF3-CEN DNA complexes was performed by combining purified CBF3 proteins with a DNA fragment that includes the CEN region from yeast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
62
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 41 publications
9
62
0
1
Order By: Relevance
“…However, the surface of the Ndc10 domain is considerably less electropositive than that of Cre (data not shown), making it unclear whether it is capable of binding DNA in the same manner. Interestingly, an atomic force microscopy study on the intact CBF3 complex (37) showed that a fraction of the complexes examined bound two DNA duplexes in a non-covalent manner, giving rise to four-armed structures. These show a marked resemblance to the recombination synapses formed by Cre, which also links two duplexes to form a four-way junction.…”
Section: Resultsmentioning
confidence: 99%
“…However, the surface of the Ndc10 domain is considerably less electropositive than that of Cre (data not shown), making it unclear whether it is capable of binding DNA in the same manner. Interestingly, an atomic force microscopy study on the intact CBF3 complex (37) showed that a fraction of the complexes examined bound two DNA duplexes in a non-covalent manner, giving rise to four-armed structures. These show a marked resemblance to the recombination synapses formed by Cre, which also links two duplexes to form a four-way junction.…”
Section: Resultsmentioning
confidence: 99%
“…Flags and plugs can be distinguished by size and location. Molecular size can be estimated according to methods described for a variety of proteins bound to mica surface (21,22) or bound to biological substrates as DNA (23,24). In short, we measured the diameter at half-maximal height of the individual molecules, which sufficiently compensates for the artificially induced overestimation of the protein width.…”
Section: Methodsmentioning
confidence: 99%
“…The reaction was terminated by phenol/chloroform extraction, and DNA was recovered by ethanol precipitation. Following the EcoRI digestion to release a promoter-containing 1.1-kb insert, DNA was 3Ј-end-labeled using [␣- 32 P]dATP and the Klenow fragment of DNA polymerase from Escherichia coli (New England Biolabs). The resultant products were separated in their single-stranded forms on a 1.5% alkaline agarose gel in 50 mM NaOH (pH 12.5), 1 mM EDTA.…”
Section: Methodsmentioning
confidence: 99%